The effect of mental cognition on some basic football skills according to performance levels of learning - Abbas, Adil; Shawkat Ibrahim, Hatem; hikmat Mahdi, Shams; Saad Ahmed, Omar (International Journal of Psychosocial Rehabilitation, 2020)
This paper contributes to the mental perception in the educational process and the necessity of codifying its size. We gave the mental perception regularly with different iterations to teach some basic skills of football for a set of beginners, average age (12-13) years. We identify the best repetition that leads to a faster learning process in every skill during every level of performance learning.